A Quantitative Method for the Measurement of Dried Blood Spot Amino Acids Using Ultra-Performance Liquid Chromatography. (15th October 2019) - Bloom, Kaitlyn; Ditewig Meyers, Gail; Bennett, Michael J
Abstract: Background: Measurement of amino acids in dried blood spots has been extensively used for the detection of newborns with various inborn errors of amino acid metabolism including phenylketonuria (PKU) and maple syrup urine disease (MSUD). Whereas blood spot amino acid measurement has been invaluable for initial diagnosis, the relative insensitivity of blood spot measurement has found limited use in lifelong monitoring of patients with these disorders. The work described here outlines the evaluation of blood spot amino acid analysis using ultra-performance liquid chromatography (UPLC © ) for use in follow-up testing. Methods: Dried blood spot amino acids were derivatized with a proprietary AccQTag ® reagent and separated using UPLC. Plasma amino acids from dried bloods spots were obtained from 318 patient samples and compared to corresponding plasma samples measured using the same UPLC method. Results: Dried blood spot amino acid concentrations were highly correlated but negatively biased vs plasma concentrations. Interassay imprecision studies using UPLC demonstrated a %CV for phenylalanine of 4.81%–16.07%, tyrosine 5.62%–20.16%, valine 4.23%–15.46%, leucine 8.3%–15.3%, and isoleucine 4.25%–16.80%. Intraassay imprecision studies using UPLC demonstrated a %CV for phenylalanine of 0.42%–3.4%, tyrosine 1.6%–7.85%, valine 0.14%–1.84%, leucine 0.28%–2.01%, and isoleucine 0.6%–2.65%. Blood spot amino acid concentrations were stable for at least 3 days at temperatures up to 65 °C. Conclusions: This UPLC-based method can reliably measure clinically significant amino acids in dried blood spots.